Chapter Alla ricerca di una 'ragionevole flessibilità' del lavoro non standard nell'intreccio di valori e tecniche - Aimo, Mariapaola (Studi e saggi, 2022)
Reasoning about the values ​​and the techniques that are pointed out in the regulation of non-standard work, the A. intends to read through this lens a couple of regulatory interventions, at internal and EU level: the 2018 reform on non-standard employment contracts, in particular on fixed-term contracts (the so-called 'Decreto dignità'), and the Directive no. 2019/1152 on transparent and predictable working conditions, that the Member States will have to implement by 2022, with a national legislation that will most probably affect the working conditions of the extreme forms of precarious work.